Macroeconomic effects of regulation and deregulation - Lakićević, Marija; Milutinović, Sonja; Žarevac, Milica (Hotel and Tourism Management, 2013)
The role of government in market economies is being discussed for more than two centuries. This problem is particularly topical in most transition countries, where the transition from a totalitarian political system and controlled economy to a multiparty, democratic system and market economy causes severe economic and social disruption. The views on the role of the government in the economy change over time because in different situations regulation and deregulation produce different effects. Particulary, the role of the government changes in the conditions of market liberalization, globalization and the creation of large multi-national corporations whose powers are greater than the power of the states. Therefore, this paper analyzes positive and negative effects of regulation and deregulation. Using comparative analysis, we concluded that a solution should be sought in an effort to strike a balance between the more intense global integration and preservation of a sufficient degree of sovereignty and cultural identity. It would be the best to keep a good performance from both sides and make a balance between regulation and deregulation. The government is there to maintain order and prevent the abuse of corporate power and size, but also to use stabilization policy when necessary. On the other hand, government should provide a free entrepreneurial initiative, equal opportunities and freedom for all people.